2015
DOI: 10.1371/journal.pone.0133616
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Antagonism Attenuates the Development of Diabetic Cardiac Fibrosis

Abstract: Heart failure (HF) is an increasingly recognized complication of diabetes. Cardiac fibrosis is an important causative mechanism of HF associated with diabetes. Recent data indicate that inflammation may be particularly important in the pathogenesis of cardiovascular fibrosis. We sought to determine the mechanism by which cardiac fibrosis develops and to specifically investigate the role of the CXCR4 axis in this process. Animals with type I diabetes (streptozotocin treated mice) or type II diabetes (Israeli Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 39 publications
5
38
0
Order By: Relevance
“…In terms of the amount of collagen, there was evidence of cellular and interstitial brosis in this experimental model, as found elsewhere for animals with diabetes [53]. Reduced myocyte hypertrophy and decreased collagen deposition ( brosis), evidencing cardiac damage, was observed in Sprague-Dawley rats trained at 80% of their maximum capacity for four weeks, showing that the high-intensity exercise was able to reverse cardiac remodeling in the diabetic heart [52].…”
Section: Discussionsupporting
confidence: 83%
“…In terms of the amount of collagen, there was evidence of cellular and interstitial brosis in this experimental model, as found elsewhere for animals with diabetes [53]. Reduced myocyte hypertrophy and decreased collagen deposition ( brosis), evidencing cardiac damage, was observed in Sprague-Dawley rats trained at 80% of their maximum capacity for four weeks, showing that the high-intensity exercise was able to reverse cardiac remodeling in the diabetic heart [52].…”
Section: Discussionsupporting
confidence: 83%
“…Is there evidence that the effects of the SDF‐1α/CXCR4 receptor axis on CFs, PGVSMCs, and GMCs observed in the present study may translate to increased cardiac and renal fibrosis in vivo? Although there is evidence that knockdown of CXCR4 receptors specifically in cardiomyoctes reduces cardiac fibrosis, studies by Chu et al demonstrated that, in mice, antagonism of CXCR4 receptors reduces cardiorenal fibrosis in mineralocorticoid‐induced hypertension and cardiac fibrosis in type 1 and 2 diabetes mellitus . Moreover, experiments by Zuk et al showed that blockade of CXCR4 receptors decreases renal fibrosis due to kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…cardiac fibrosis, 20 studies by Chu et al demonstrated that, in mice, antagonism of CXCR4 receptors reduces cardiorenal fibrosis in mineralocorticoid-induced hypertension 21 and cardiac fibrosis in type 1 and 2 diabetes mellitus. 22 Moreover, experiments by Zuk et al 23 showed that blockade of CXCR4 receptors decreases renal fibrosis due to kidney injury. In addition, Yuan et al 24 reported that CXCR4 receptor expression is increased in ureteral obstruction and that CXCR4 receptor knockout prevents hydronephrosis-induced renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although myocardial MCP-1 expression was increased in a rat model of type 2 diabetes [106], whether induction of the chemokine plays a critical role in fibrosis of the diabetic heart has not been investigated. SDF-1 blockade through inhibition of its receptor CXCR4 attenuated cardiac fibrosis in rodent models of type 1 and type 2 diabetes [107]. …”
Section: Molecular Signals Implicated In Diabetes-associated Cardimentioning
confidence: 99%